Multiplex PCR for Simultaneous Detection of Virulence Genes in Escherichia coli - Thong, Kwai Lin; Yu, Ke Xin (Faculty of Science, University of Malaya, 2009)
Diarrhea caused by Escherichia coli infection is a major cause of public health problems in developing countries. In view of the deficits and limitations of conventional methods of detecting the virulence determinants, a multiplex Polymerase Chain Reaction (PCR) assay was optimized and developed to provide an effective, rapid and specific diagnostic tool to simultaneously detect virulence genes such as heatstable toxin 1 (ST1), heat-labile toxin 1 (LT1), heat-labile toxin 2 (LT2), verotoxin1 (VT1), verotoxin 2 (VT2) and attachment and effacement (eaeA) in pathogenic E. coli. Five sets of primers targeting these six virulence genes were optimized by using postitive control E. coli strains. The optimized conditions consisted of 3.0 mM of MgCl2, 0.2 mM of dNTPs, 1.5 U of Taq DNA polymerase (Promega), 0.70 µM of VT primer, 0.60 µM of LT2 primer and 0.07 µM each of LT1 primer, ST primer and AE primer. The mPCR assay was then applied to a panel of 87 E. coli isolates from different sources. One food isolate (EC 375) was positive for eaeA gene while another environmental isolate had ST, LT1, eaeA and VT genes. The study shows that the mPCR assay is a useful tool to differentiate the pathogenic potential (pathotypes) of E. coli by presence of known virulence genes.